"History, but normal!" : On the Derailment of the Present from the Tracks of History (KULT_online, 2024)
In the sociological dissertation Rechte Zeitverhältnisse, Philipp Rhein examines right-wing populist concepts of time. He analyzes interviews for the temporal orientation of AfD voters. His core thesis is that right-wing populism is a reaction to the time crisis of late modernity (Spätmoderne). The guiding principle is not the loss of the past, but of the future, which is distilled in the figure of right-wing populist chiliasm. Rhein’s analysis thus offers an important insight into the temporal perception of the right-wing electorate.